2006
DOI: 10.1038/sj.jhh.1002017
|View full text |Cite
|
Sign up to set email alerts
|

Absence of association between depression and hypertension: results of a prospectively designed population-based study

Abstract: The objective of this study was to examine the relation between hypertension and depression. In a crosssectional study of the urban region of a State capital with more than 1.5 million inhabitants, 1174 men and women aged 18-80 years, selected at random from the population, were studied. Blood pressure, hypertension (blood pressure readings X140/90 mm Hg or use of blood pressure-lowering agents), risk factors for hypertension and depression according to the Diagnostic and Statistical Manual of Mental Disorders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
40
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(48 citation statements)
references
References 31 publications
5
40
0
2
Order By: Relevance
“…45 The seven studies that screened for major depressive disorder used the following tools: the Composite International Diagnostic Interview (CIDI), 22,43,44,[50][51][52][55][56][57][58][59][60][61] the Mini-International Neuropsychiatric Interview (MINI), [36][37][38][39] and the DSM-IV. 41 The mean quality score was 5.8. Three studies scored fewer than five points.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations
“…45 The seven studies that screened for major depressive disorder used the following tools: the Composite International Diagnostic Interview (CIDI), 22,43,44,[50][51][52][55][56][57][58][59][60][61] the Mini-International Neuropsychiatric Interview (MINI), [36][37][38][39] and the DSM-IV. 41 The mean quality score was 5.8. Three studies scored fewer than five points.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Most of the surveys included persons 18 years old and older. [22][23][24][25][26][27][28][29][36][37][38]40,41,43,44,[50][51][52][55][56][57][58][59][60][61][62][63] Three studies did not primarily aim to assess the prevalence of depression. 30,35,47 Six national studies were included.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…A quantitative review identified that psychological factors could be associate with hypertension, 5 but the isolate contribution of each component has been questioned. 32 To our knowledge, this is the first systematic review addressing the association between stress and hypertension in cohort and case-control studies. We had planned to undertake a meta-analysis, but the heterogeneity between the studies, with regard to design, definition of exposure and outcome and control for confounding, excluded this possibility.…”
Section: Stress and Hypertension F Sparrenberger Et Almentioning
confidence: 99%